Mengajarkan Pancasila Melalui Puisi Berjudul “Pancasila Dasar Negara” Karya: Misnawati - Anwarsani Anwarsani; Erniwati Erniwati; Mahdalena Mahdalena; Apianson Apianson; Hifzatun Najmi; Suwartini Suwartini; Sri Triwindra; Anni Millasari; Devi Kristiyaningsih; Haris Fadillah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This article discusses a poem entitled